Dysregulation of Subcutaneous White Adipose Tissue Inflammatory Environment Modelling in Non-Insulin Resistant Obesity and Responses to Omega-3 Fatty Acids – A Double Blind, Randomised Clinical Trial - Fisk, Helena L.; Childs, Caroline E.; Miles, Elizabeth A.; Ayres, Robert; Noakes, Paul S.; Paras-Chavez, Carolina; Antoun, Elie; Lillycrop, Karen A.; Calder, Philip C. (Frontiers in Immunology, 2022)
Background Obesity is associated with enhanced lipid accumulation and the expansion of adipose tissue accompanied by hypoxia and inflammatory signalling. Investigation in human subcutaneous white adipose tissue (scWAT) in people living with obesity in which metabolic complications such as insulin resistance are yet to manifest is limited, and the mechanisms by which these processes are dysregulated are not well elucidated. Long chain omega-3 polyunsaturated fatty acids (LC n-3 PUFAs) have been shown to modulate the expression of genes associated with lipid accumulation and collagen deposition and reduce the number of inflammatory macrophages in adipose tissue from individuals with insulin resistance. Therefore, these lipids may have positive actions on obesity associated scWAT hypertrophy and inflammation. Methods To evaluate obesity-associated tissue remodelling and responses to LC n-3 PUFAs, abdominal scWAT biopsies were collected from normal weight individuals and those living with obesity prior to and following 12-week intervention with marine LC n-3 PUFAs (1.1 g EPA + 0.8 g DHA daily). RNA sequencing, qRT-PCR, and histochemical staining were used to assess remodelling- and inflammatory-associated gene expression, tissue morphology and macrophage infiltration. Results Obesity was associated with scWAT hypertrophy (P < 0.001), hypoxia, remodelling, and inflammatory macrophage infiltration (P = 0.023). Furthermore, we highlight the novel dysregulation of Wnt signalling in scWAT in non-insulin resistant obesity. LC n-3 PUFAs beneficially modulated the scWAT environment through downregulating the expression of genes associated with inflammatory and remodelling pathways (P <0.001), but there were altered outcomes in individuals living with obesity in comparison to normal weight individuals. Conclusion Our data identify dysregulation of Wnt signalling, hypoxia, and hypertrophy, and enhanced macrophage infiltration in scWAT in non-insulin resistant obesity. LC n-3 PUFAs modulate some of these processes, especially in normal weight individuals which may be preventative and limit the development of restrictive and inflammatory scWAT in the development of obesity. We conclude that a higher dose or longer duration of LC n-3 PUFA intervention may be needed to reduce obesity-associated scWAT inflammation and promote tissue homeostasis. Clinical Trial Registration www.isrctn.com, identifier ISRCTN96712688.